2003
DOI: 10.1124/dmd.31.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Metabolism of the Reactive Oxygen Scavenger α-Phenyl-N-tert-butylnitrone in the Male Sprague-Dawley Rat

Abstract: ABSTRACT:The pharmacokinetics of the spin-trap ␣-phenyl-N-tert-butylnitrone (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Trudeau-Lame et al reported that plasma concentrations after i.v. PBN (10 mg/kg) administration declined rapidly with a terminal halflife of 2.01 ± 0.35 h in male Sprague-Dawley rats and also total plasma clearance and volume of distribution at steady state averaged 12.37 ± 3.82 ml/min/kg and 1.74 ± 0.5 l/kg, respectively [17]. Whereas PBN has got considerably low in vivo stability and short blood residence time we prepared nanocarrier systems using different biodegradable polymers modified with PEG chain.…”
Section: Discussionmentioning
confidence: 99%
“…Trudeau-Lame et al reported that plasma concentrations after i.v. PBN (10 mg/kg) administration declined rapidly with a terminal halflife of 2.01 ± 0.35 h in male Sprague-Dawley rats and also total plasma clearance and volume of distribution at steady state averaged 12.37 ± 3.82 ml/min/kg and 1.74 ± 0.5 l/kg, respectively [17]. Whereas PBN has got considerably low in vivo stability and short blood residence time we prepared nanocarrier systems using different biodegradable polymers modified with PEG chain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the circulatory half-life observed for STAZN is much longer than the 2 h half-life for PBN in rats (Trudeau-Lame et al, 2003). Less than 0.5% of a dose of PBN can be found unchanged in the urine, but rather, most of this drug is metabolized in the liver (TrudeauLame et al, 2003;Lame et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Two doses were used to allow for the plasma half-life of PBN (terminal half-life in rat $2 h). 31 At 240 min, animals were killed by cervical dislocation, brains rapidly removed, cerebella discarded and cerebral hemispheres frozen in liquid nitrogen. Whole hemispheres were homogenized in Trizol, total RNA extracted and cleaned using RNeasy columns (QIAGEN GmbH, Hilden, Germany).…”
Section: Microarray Analysismentioning
confidence: 99%